2023
DOI: 10.3390/diagnostics13142452
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Colonoscopy and Beyond: Insights into Modern Lower Gastrointestinal Endoscopy

Abstract: Lower gastrointestinal endoscopy is considered the gold standard for the diagnosis and removal of colonic polyps. Delays in colonoscopy following a positive fecal immunochemical test increase the likelihood of advanced adenomas and colorectal cancer (CRC) occurrence. However, patients may refuse to undergo conventional colonoscopy (CC) due to fear of possible risks and pain or discomfort. In this regard, patients undergoing CC frequently require sedation to better tolerate the procedure, increasing the risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…Its larger size relative to microscopic objects can potentially cause discomfort or injury to patients during the procedure. Moreover, there are inherent limitations in observing and operating in certain blind spots within the intestine during examinations ( Tapia-Siles et al, 2016 ; Tumino et al, 2023 ). In response to these challenges, technological advancements have led to the development of non-invasive endoscopic capsules and capsule endoscopes that can actively navigate within the intestinal tract under magnetic field guidance.…”
Section: Application Of Micro/nanorobot In Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Its larger size relative to microscopic objects can potentially cause discomfort or injury to patients during the procedure. Moreover, there are inherent limitations in observing and operating in certain blind spots within the intestine during examinations ( Tapia-Siles et al, 2016 ; Tumino et al, 2023 ). In response to these challenges, technological advancements have led to the development of non-invasive endoscopic capsules and capsule endoscopes that can actively navigate within the intestinal tract under magnetic field guidance.…”
Section: Application Of Micro/nanorobot In Medicinementioning
confidence: 99%
“…While Chimeric Antigen Receptor T (CAR-T) cell therapy has shown promise in treating hematological malignancies, its efficacy in solid tumors is curtailed by physical barriers and the immune microenvironment (Ma et al, 2019;Li et al, 2021). Addressing this, Tang et al (2023) have engineered a living micro-robot using CAR-T cells, which are augmented with immune magnetic beads through click conjugation (see in Figure 3D). This construct is magnetically steerable and capable of navigating fluids and circumventing obstacles.…”
Section: Targeting Drug Deliverymentioning
confidence: 99%
“…While endoscopy proves effective in early disease detection, thereby enhancing patient survival and reducing treatment costs, it is not without associated complications [6]. Anxiety emerges as a fundamental concern for patients undergoing diagnostic and therapeutic procedures [7], representing an unpleasant state of worry or pressure prevalent in various facets of human life [8]. Elevated anxiety levels during invasive procedures like endoscopy not only contribute to complications but also result in adverse effects, prolonged procedure times, increased sedative drug requirements, and hindered patient recovery [1].…”
Section: │ Introductionmentioning
confidence: 99%
“…Previous research has yielded varied outcomes regarding factors influencing anxiety in endoscopy patients [1]. In the realm of nursing studies, a predominant focus revolves around the objective of pain relief in patient care [7]. Numerous studies have demonstrated the positive impact of interventions such as music therapy and relaxation on alleviating pain and anxiety in individuals undergoing endoscopy [4].…”
Section: │ Introductionmentioning
confidence: 99%